MENERAPKAN SIKAP DAN PERILAKU YANG BERPRINSIP PADA BHINNEKA TUNGGAL IKA DI ERA 4.0 DALAM PEMBELAJARAN K13 DI MI/SD KELAS IV - Astuti, Arifian Dwi; Nur Farida, Mila Wati; Zuhri, Anis Fuadah (PD PGMI se Indonesia, 2020)
Indonesia is one of the countries in the world and is the largest multicultural country. Diversity is doesn’t only discuss the issue of race, but about religion, ethnicity, customs, and language. Each region has a different character and makes it the unique characteristic of the region. Diversity is one of the assets owned by the Indonesian state, but with the diversity it can trigger conflicts and divisions, ranging from racial, religious, ethnic, and cultural discrimination. In addition, the development of the era in the 4.0 era can also affect the occurrence of conflict. In this era a lot of technology continues to develop, so that many foreign cultures enter Indonesia easily, and can reduce the sense of patriotism. These problems can be overcome by applying attitudes that reflect the values of Pancasila and the value of Bhinneka Tunggal Ika. The Indonesian motto of Indonesian people is Bhinneka Tunggal Ika, the motto has different meanings but it remains one. Bhinneka Tunggal Ika is applied by Indonesia to reflect the value of unity and unity which aims to maintain the integrity of the Unitary State of the Republic Indonesia. Understanding the values of Bhinneka Tunggal Ika in multicultural societies is used as a pillar of nationalism, because it contains the values of tolerance and the value of justice. Generally tolerance and justice develop because of differences in people's lives. This paper aims to explain the importance of Bhinneka Tunggal Ika values in the implementation of daily life, espessially in the era of 4.0.